Albula gilberti, a new species of bonefish (Albuliformes: Albulidae) from the eastern Pacific, and a description of adults of the parapatric A. esuncula - Pfeiler, Edward; van Der Heiden, Albert M.; Ruboyianes, Ryan S.; Watts, Tom (Zootaxa, 2011)
A new species of bonefish (Albuliformes: Albulidae: Albulinae) from the eastern Pacific Ocean, Albula gilberti, is described. Previously referred to as Albula sp. A, A. gilberti is distributed throughout the Gulf of California, Mexico to the coastal waters of California, USA. Presently, it can be distinguished from its closest relative, A. esuncula (= Albula sp. C) from the tropical eastern Pacific, solely by differences in mitochondrial DNA (cytochrome b) gene sequences. No diagnostic external morphological characters have yet been found that can reliably separate the two distinct genetic lineages although some differences in placement of pelvic-fin tip relative to vent may exist. Differences detected in counts of meristic characters should be tested in larger series of specimens, especially of A. esuncula. Available evidence also suggests that A. gilberti and A. esuncula show a parapatric distribution, with an area of sympatry in the southern Gulf of California. We also provide a description of adults of A. esuncula (the original description was based solely on two larvae), review the current nomenclature of the subfamily Albulinae, and discuss the role and justification of using molecular data for diagnosing cryptic species.